DESCRIPTION OF SERVICES PER CONCEPTION, CONCEPTION RATE AND PREGNANCY RATE IN DAIRY CATTLE POST FOOT AND MOUTH DISEASE AT KPSBU LEMBANG - Miftahuljannah, Maulyda Ahmad; Septiyani, Septiyani; Solihati, Nucholidah (Fakultas Peternakan, Universitas Padjadjaran, 2024)
The availability of dairy cow milk in Indonesia is still insufficient to meet domestic needs, one of which is caused by the declining dairy cow population due to infectious diseases, namely FMD (Foot and Mouth Disease). Not only does it cause economic losses, FMD also results in a decline in the reproductive status of dairy cows. To assess whether a cow's productivity level is good or not, it can be determined quantitatively by calculating several reproductive efficiency parameters, namely Service per Conception (S/C), Conception Rate (CR) and Pregnancy Rate (PR). The aim of this research is to describe the reproductive efficiency of post-FMD dairy cows based on S/C, CR and PR values. This research used a descriptive approach to data from 1,046 sample animals taken from the KPSBU Lembang recording system, which was then tabulated using the Excel program. Based on the calculation results of reproductive efficiency parameters, the S/C value was obtained, namely 1.635 times, where this value is in the normal category. Meanwhile, for the CR and PR parameters, the values obtained are 49% and 61%, which shows that these values are below the normal.